A GESTÃO AMBIENTAL E A SUSTENTABILIDADE DAS EMPRESAS DE TRANSPORTE COLETIVO URBANO DE PASSAGEIROS: ANÁLISE DE EMPRESAS DE TRANSPORTE DO RIO DE JANEIRO - Cavalheiro, Ronaldo da Silva (2003)
The urban public transport segment of bus passengers is strategic in the development. However, the change in the competitive environment in the last decade was faster and deeper than their managers had expected. The competitive atmosphere which the sector is being obliged to face, and added to its new demands, is determining new management models and forms so as to keep the sector and business sustainability. Considering this scenario, among other important factors, the environmental issues were observed as vectors, which may assist in the business sustainability. Therefore, this project intends to argue and present the main environmental subjects of the sector and how these ones influence the sustainability of the urban transport companies. Furthermore, the project will verify the track level (level of adherence to/level of adhesion to) to the environmental issues. This project ponders the analysis of some urban transport companies culminating in the attainment of data on practices as well as difficulties concerning environmental issues.